1999
DOI: 10.1034/j.1600-0420.1999.770606.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C resistance and anticoagulant proteins in young adults with central retinal vein occlusion

Abstract: ABSTRACT.Background: Central retinal vein occlusion is a disease that is most common in old people, and often associated with atherosclerosis, hypertension, diabetes or glaucoma. Since these diseases are much less evident in young people, we wanted to investigate the prevalence of disorders in the most common anticoagulant proteins in a group of young patients with central retinal vein occlusion. Methods. 37 consecutive patients younger than 50 years and with a history of central retinal vein occlusion, were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
3
29
1
1
Order By: Relevance
“…Larsson et al in a study of 37 patients found no cases of plasminogen deficiency (incidence of 0.3% in the normal population). 17 Williamson found normal levels of tissue plasminogen activator but significantly low levels of plasminogen activator inhibitor (PAI) (P = 0.03) indicating a hypofibrinolytic state in his 87 patients with CRVO. 23 The high levels of PAI were confirmed by Gleuk et al who also showed, in 17 patients, a significantly higher level of the 4G/4G and 4G/5G polymorphisms of the PAI gene (P = 0.03).…”
Section: Abnormalities Of Fibrinolysismentioning
confidence: 99%
See 3 more Smart Citations
“…Larsson et al in a study of 37 patients found no cases of plasminogen deficiency (incidence of 0.3% in the normal population). 17 Williamson found normal levels of tissue plasminogen activator but significantly low levels of plasminogen activator inhibitor (PAI) (P = 0.03) indicating a hypofibrinolytic state in his 87 patients with CRVO. 23 The high levels of PAI were confirmed by Gleuk et al who also showed, in 17 patients, a significantly higher level of the 4G/4G and 4G/5G polymorphisms of the PAI gene (P = 0.03).…”
Section: Abnormalities Of Fibrinolysismentioning
confidence: 99%
“…Similarly in a study of 37 patients aged Ͻ50 years, three (8%) were found to have deficiency of protein C, protein S or ATIII. 17 Tekeli et al found protein C deficiency in 20% (9/45) of patients with either central or branch vein occlusion. 18 He also identified two cases of protein S deficiency and one of ATIII deficiency, giving an incidence of naturally occurring anticoagulant deficiency of 27% overall.…”
Section: Protein C Protein S and Anti-thrombin Iii Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, in the case of bilateral and recurrent CRVO, a systemic cause should be suspected, especially a hyperviscosity or hypercoagulation state, such as abnormal platelet function or anticoagulant protein deficiencies. 5,6 Local ocular conditions such as uncontrolled glaucoma and optic nerve drusen 4,7 should also be excluded in unilateral cases, as these conditions have been reported in association with CRVO.…”
Section: Discussionmentioning
confidence: 99%